Research Productivity on Manuscripts in the field of Social Science (2010-2020). Scopus Database - Tyagi, Sunil (Bibliotecas. Anales de investigación, 2022)
The study aimed to assess and analyze the research productivity on manuscripts in the field of social science on a set of quantitative and qualitative metrics to discover underlying research trends at global, national, organizational and individual level. The study is based on 11 years’ global research data (N=1136) on the topic sourced from Scopus database for the time span 2010-2020. The scientometric analysis used to assess the research productivity. The research productivity on manuscripts registered 17.21 per cent annual average growth and 6.36 per cent compound annual growth rate with an average citation impact of 1.42 citations per paper. The average number of authors per paper was 1.29 and the average productivity per author was 0.79. The resultant data indicates that the degree of collaboration ranges between 0.13≥0.24 and the overall degree of collaboration was 0.17. The Pearson correlation analysis inferred a significant and positive relationship (r = 0.889, N = 11, p =0.000) between number of articles and the number of authors.